It's a doggy dog world - Greenwald, Tom, 1962- (Greenwald, Tom, 1962- Crime biters! ;, 2016)
Bored by the lack of crime in Quietville lately, Jimmy's vampire dog, Abby, has chewed up his mother's entire shoe collection, and so his parents have insisted in enrolling Abby in obedience training, and the longer it goes on the more "normal" (and boring) she becomes--but when mysterious things start happening to Jimmy's lacrosse team, he and his friends (the Crimebiters) realize they need to get Abby back to her crime fighting ways.